Persahabatan antara Tuhan dan Manusia dalam Doa: Sebuah Refleksi Teologis Pemikiran Teresa Avila - Wicaksono, Agung (Institutum Theologicum Ioannis Mariae Vianney Surabayanum, 2023)
In the Christian faith, prayer is seen as a relationship between humans and the Divine. Related to this, Christians can find a quintessential example in the person of Jesus Christ himself. As the Son of God, through prayer, Jesus manifested the intimate, intense, and indissoluble union of the three persons of the Triune God: the Father, the Son, and the Holy Spirit. As a human, through prayer, Jesus demonstrated to us how humans should relate to the Divine which shows a close union. Together with Teresa of Avila, we are going to see that relationship between humans and the Divine is a true communion in which interpersonal closeness is possible, as if between close friends.